Cultivating teacher expertise : The role of pedagogical training in shaping life science university teachers’ professional vision and conceptions of teaching and learning - Heinonen, Neea; Katajavuori, Nina; Ketonen, Elina; Murtonen, Mari; Södervik, Ilona (LUMA Centre Finland, 2026)
This study investigated how life science university teachers’ professional vision, that is, their ability to notice and interpret pedagogically significant incidents in the classroom, was related to their (mis)conceptions of teaching and learning at the beginning of pedagogical training, and how these changed after the training. In addition, we examined whether distinct teacher profiles could be identified based on their conceptions of teaching and learning, and how these profiles differed in their professional vision before and after pedagogical training. A total of 127 life science university teachers from the University of Helsinki filled in a questionnaire and completed a video interpretation task. A pre-test / post-test design was used, and data were analysed quantitatively. This study shows that life science university teachers’ professional vision and conceptual understanding were related. In the pre-test, participants with fewer misconceptions tended to notice more pedagogically significant incidents compared to participants with more misconceptions. Statistically significant improvements were found in participants’ professional vision after pedagogical training. Additionally, participants’ conceptions became more scientific. In the post-test, more sophisticated conceptions of teaching and learning were related to better skills in both noticing and interpreting a classroom video. These findings suggest that life science university teachers’ professional vision may vary depending on their conceptual understanding that guides their noticing and interpreting of pedagogically relevant events in the classroom. Moreover, the cluster analysis revealed distinct teacher profiles based on their conceptions, which differed in their development of noticing skills from pre-test to post-test.